2019
DOI: 10.1002/pat.4770
|View full text |Cite
|
Sign up to set email alerts
|

An inorganic route to decorate graphene oxide with nanosilica and investigate its effect on anti‐corrosion property of waterborne epoxy

Abstract: This paper reported an inorganic route that uses potassium silicate, which is one type of alkali silicate as an inorganic modifier, taking advantage of its instability and water condensation to decorate graphene oxide (GO) with nano-SiO 2 . The ingredients of prepared nanocomposites were characterized by Fourier-transform infrared spectroscopy (FT-IR) and X-ray photoelectron spectroscopy (XPS), and the thermodynamic property was tested by thermal gravimetric analysis (TGA). Scanning electron microscopy (SEM) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 44 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…In addition, the weak peak at 1532 cm –1 was ascribed to the secondary amide N–H bending, and the N–H vibration peak could be observed at 814 cm –1 as well. Moreover, the C–N tensile peak and Si–O–C peak arose at 1456 and 1072 cm –1 , respectively. These results vividly demonstrated that the GO was modified by GPTS and the nanocomposite SiO 2 -GO was prepared.…”
Section: Resultsmentioning
confidence: 77%
“…In addition, the weak peak at 1532 cm –1 was ascribed to the secondary amide N–H bending, and the N–H vibration peak could be observed at 814 cm –1 as well. Moreover, the C–N tensile peak and Si–O–C peak arose at 1456 and 1072 cm –1 , respectively. These results vividly demonstrated that the GO was modified by GPTS and the nanocomposite SiO 2 -GO was prepared.…”
Section: Resultsmentioning
confidence: 77%
“…Compared with previous methods, this synthesis is relatively simple. [44] Besides the method of in-situ formation on the surface of graphene oxide, grafting nano-SiO 2 onto the surface of graphene oxide by silane coupling agent is also a common method. Pourhashem et al compared the effects of APTES and GPTMS on the performance of nanocomposite coatings.…”
Section: Grafting Nano-silica On the Surface Of Graphene Oxidementioning
confidence: 99%
“…The test results showed that SiO 2 ‐GO had good dispersion in epoxy resin coatings and enhanced the barrier properties of the coatings. Compared with previous methods, this synthesis is relatively simple [44] …”
Section: Graphene Oxide Coating and Its Corrosion Protection Performancementioning
confidence: 99%
“…The interest in SiO 2 nanoparticles stems from their excellent chemical and thermal stability, hydrophilicity and low cost. A number of studies have shown that SiO 2 -modifed GO epoxy coatings have more protective properties than the corresponding GO/epoxy formulations with the nano-SiO 2 playing an important role in improving the dispersion of GO sheets [233,234]. When GO is modified with SiO 2 it becomes more hydrophilic and while this improves its dispersion within coatings, it can also reduce the protective nature of the coatings.…”
Section: Nanoparticle Decorated and Metal Oxide Modified Graphenementioning
confidence: 99%